Music Creation Waringin | Tabuh Kreasi Waringin - Putu Arya Krisna Devantara; I Made Dwi Andika Putra (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
In Balinese Hinduism, the banyan tree is one of the most sacred trees because it is believed to have religious values. For the creator, visually it can be seen from the roots that hang above and also spread underground, reflecting two interrelated beliefs, namely belief in Ida Sang Hyang Widhi Wasa/God Almighty and life in the universe. Its large trunk symbolizes strength and shady leaves, as a whole, can provide shade for the world's universe. From the explanation above, the creator was very interested in the existence of the banyan tree, so he was inspired to transform the object in question into a creation of Tabuh Kreasi Pepanggulan entitled